2021
DOI: 10.1101/2021.02.08.21251070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The protective association between statins use and adverse outcomes among COVID-19 patients: a systematic review and meta-analysis

Abstract: Introduction: Statins may reduce a cytokine storm, which has been hypothesized as a possible mechanism of severe COVID-19 pneumonia. The aim of this study was to conduct a systematic review and meta-analysis to report on adverse outcomes among COVID-19 patients by statin usage. Methods: Literatures were searched from January 2019 to December 2020 to identify studies that reported the association between statin usage and adverse outcomes, including mortality, ICU admissions, and mechanical ventilation. Studies… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Another meta-analysis indicated that patients receiving statins after COVID-19 diagnosis were at lower risk of mortality relative to non-statin patients (37). A lower disease severity was also reported in COVID-19 patients receiving statins (38).…”
Section: Fig 1 Blocking Angiotensin-converting Enzyme 2 (Ace2) As a Result/because Of Sars-cov-2 Infectionmentioning
confidence: 95%
“…Another meta-analysis indicated that patients receiving statins after COVID-19 diagnosis were at lower risk of mortality relative to non-statin patients (37). A lower disease severity was also reported in COVID-19 patients receiving statins (38).…”
Section: Fig 1 Blocking Angiotensin-converting Enzyme 2 (Ace2) As a Result/because Of Sars-cov-2 Infectionmentioning
confidence: 95%
“…There is currently no safe treatment for patients with non-severe COVID-19. Given the results of our prior systematic review 7 , and now this cost-effectiveness analysis suggesting statin-containing treatments are both cheaper and more effective, statins should be further investigated for use in non-severe COVID-19 patients. Statin therapy may lead to side effects of myopathy and liver toxicity, but these adverse events typically reverse, after discontinuation of statins.…”
Section: Discussionmentioning
confidence: 98%
“…We assumed that probabilities reported by Rodriguez-Nava et al 6 were 4-week probabilities, and computed 1-week probability from it. Probability of death among statin patients was computed, using relative risks reported from a prior meta-analysis (Chow et al 7 ) and the probability reported by Zhang et al 5 for non-statin patients. Probability of discharge and ICU admissions among statin patients was also sourced from Zhang et al 5 ; probability of death among ICU patients receiving statins was extracted from Rodriguez-Nava et al 6 .…”
Section: Probabilitiesmentioning
confidence: 99%
“…perpetuity. preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted August 1, 2021. ; https://doi.org/10.1101/2021.07.30.21261329 doi: medRxiv preprint hospitalization, but no difference in patients who were administered statins before hospitalization 19 . Although there is a lack of consensus among data on statin's efficacy and safety amongst COVID-19 patients, the current recommendation is for COVID-19 patients to continue any antecedent statin use 20 .…”
Section: Introductionmentioning
confidence: 98%
“…While Zhang et al 9 and Rodriguez-Nava et al 10 report that statin reduced the risk of mortality and/or disease severity, and Wang et al 11 reported an increased mortality among statin users, other studies [12][13][14][15][16][17][18] report no significant difference between statin users and non-users. Meanwhile, a recent systematic review and meta-analysis of 110,078 patients reported a reduced risk of mortality among those administered statins after their COVID- 19 hospitalization, but no difference in patients who were administered statins before hospitalization 19 . Although there is a lack of consensus among data on statin's efficacy and safety amongst COVID-19 patients, the current recommendation is for COVID-19 patients to continue any antecedent statin use 20 .…”
Section: Introductionmentioning
confidence: 99%